Outcomes of Propofol or Thiopental Sodium and Oral Midazolam as an Induction Agent for Day Care Surgery - Fazal Wadood, Mohammad Javed, Umbrin Naz, Shahid Maqsood, Ambareen Sifatullah, Abid Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acceptance of day surgery has been steadily rising for over a decade. Day surgery is essential in developing countries since it allows for quick healing and lower overall costs. Day surgeries have been on the rise in recent years. Induction agents like propofol and thiopentone are frequently utilized during outpatient procedures. This study aimed to compare ASA grade I and II patients undergoing day surgery, the compass reading time, hemodynamic comeback, respiratory upshots, and the postoperative resurgence of the two medications. Objective: Oral midazolam, thiopental sodium, and propofol were all used for induction before day surgery. The goal was to determine which method was most cost-effective and resulted in the quickest recovery. Methodology: The study was conducted at Khyber Teaching Hospital, Peshawar, Pakistan from February, 2023 to July, 2023. A total of sixty patients were selected, practically thirty from one of ASA's top two health tiers. In group A, patients were given 2.0 mg/kg of propofol for compass reading, while in group B, patients were given 0.250 mg/kg of oral midazolam 30 minutes prior they were prearranged 2.50 mg/kg of thiopental sodium for induction. During the operation, doctors kept tabs on the patient's vital signs, BP, recuperation score, and ability to return home. For both groups, we calculated the typical price of induction. Result: After 30 minutes of reverse, group A scored 8.8± 1.75, and group B scored 8.01± 1.03. Group B's costs (BDT 37.88±1.37) were considerably lower than A's (BDT 142.00±6.00), with a P value of< 0.05. Conclusion: For outpatient surgeries, using vocal midazolam and low- a prescribed amount of thiopental sodium orientation is more cost- effectual than propofol induction. Keywords: Day care surgery, Oral midazolam, thiopental sodium, propofol.